Glaucoma, "the silent thief of sight": patients' perspectives and health seeking behaviour in Bauchi, northern Nigeria. Issue 1 (December 2016) - Abdull, Mohammed; Chandler, Clare; Gilbert, Clare
Abstract Background In Nigeria, glaucoma has a high prevalence and is the second cause of blindness among adults after cataract. People with glaucoma frequently present very late with advanced disease, and acceptance of and adherence to treatment is low. The purpose of the study was to explore how patients' understand and respond to glaucoma in order develop an intervention to improve adherence to treatment. Method Hospital based qualitative study. Six focus group discussions were held with patients with advanced disease and who had either undergone glaucoma surgery, were receiving medical treatment, or had neither surgery nor medical treatment. Two traditional healers who treat eye conditions were interviewed. Audio files were transcribed, translated into English and recurring themes coded and categorized as the impact of vision loss, and understandings of the disease and its management. Results Visual loss impacted significantly on the lives of people with glaucoma in many ways. Many heard the term "glaucoma" for the first time during the study. Local terms to describe the symptoms includedHawan jinin ido ("hypertension of the eye"). Patients sought treatment in pharmacies, or with traditional healers who had different interpretations of glaucoma and its treatment to biomedical understandings. Cost and forgetfulness were the main reasons for low adherence to treatment while fear was a reason for not accepting surgery. Lack of money and negative staff attitudes were reasons for low follow up. Conclusion Halting the progression of glaucoma is possible with treatment but the condition will remain a "silent thief of sight" in West Africa unless awareness, uptake of services and adherence to treatment improve. Understanding how glaucoma is locally conceptualised, lived with and responded to by patients is essential to aid the design of interventions to prevent glaucoma blindness in Africa. Findings have been used to adapt a motivational interviewing intervention, which is being evaluated in a clinical trial.